THOMAS MÜNTZER: A HISTORICAL CATALYST IN GERMAN PEASANTS WAR - Emre Taşkıran (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
In this article, Thomas Müntzer, the leading historical figure in the German Peasants War, is scrutinized in a different context within the perspective of the social history of political thought. By choosing the mainstream literature, this study has used some of the important pamphlets, letters, and secondary qualitative texts on Müntzer’s manuscripts about both the German Peasants War and his theological assertations toward the Reformation process which began with Martin Luther’s contributions to Catholic Church in 16th century. Examining social, political, and theological dynamics in the 16th century German Reformation process, this article has tried to find the potential answers to the basic question, which is how contradicted theological conflict between prominent Protestant doctrines led to revolutionary tendencies among exploited groups in German Reformation Process. In this respect, Müntzer is described as a historical catalyst who combines the revolutionary dynamics with the theological assumptions under the identity of a reformist cleric.